The food safety hazard guidebook - Lawley, Richard (RSC Publishing, 2012)
Consumers have a right to expect that the food industry has taken care to ensure their products are safe to eat. Those with regulatory responsibility recognize this principle and legislate accordingly. This guidebook acts as a portal for the immense and ever expanding body of scientific knowledge on food safety. It is unique in its coverage of a very wide range of food safety hazards, both biological and chemical. Each chapter follows the same risk analysis-based structure to enable the reader to find information easily. Up-to-date sources of additional facts, published and web-based, are supplied for every hazard. The book can, therefore, be used as a first port of call for locating information on almost all known food safety hazards. The new Second Edition retains the format and structure of the original and continues to provide a concise, accessible and affordable source of reference. The information on each hazard has been reviewed and up-dated to reflect recent changes. Additional information on approximately 15 potential and emerging food safety hazards, not covered in the first edition, has been added. An entirely new section, covering the basic principles and practice of Hazard Analysis Critical Control Point (HACCP) and food safety management systems, has been introduced. The section on food-borne bacterial pathogens has been thoroughly up-dated and the section on fish toxins has been revised in line with the current classification of marine biotoxins. This highly usable working companion for food industry professionals, is an indispensable resource for food scientists worldwide.
Previous edition: 2008.
Keywords: Food -- Microbiology -- Handbooks, manuals, etc.; Food handling -- Handbooks, manuals, etc.; Food poisoning -- Handbooks, manuals, etc.; Food contamination.; Food -- Toxicology.; Allergens.; elektronické knihy; electronic books